If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 4g = c Reorder the terms: 4g + 5x = c Solving 4g + 5x = c Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-5x' to each side of the equation. 4g + 5x + -5x = c + -5x Combine like terms: 5x + -5x = 0 4g + 0 = c + -5x 4g = c + -5x Divide each side by '4'. g = 0.25c + -1.25x Simplifying g = 0.25c + -1.25x
| 8=-3x+2(x-4) | | 6-2x=22 | | 4g+7=4g-1 | | 4(2x+1)-3(y+1)= | | -2=-1.75+k | | 12r^2-75=0 | | -2=7+k/(-4) | | 4(w+3)=w- 15 | | X=3x+12 | | 40+400+1= | | 7(3-y)=-3x+4 | | 21x+6=17x-16 | | -d^2+18d-81=0 | | -13X+20=-11 | | (5x-20)=3x | | 7h-3h-6=6 | | 5(x-1)(x+4)(2x-3)=0 | | -2=-1.75k | | 25=5(9x-4) | | 2x-9=6x-13 | | -2(3)+5+5(3)= | | 6x-2=12x+1 | | 2x^3-3x-20=0 | | y-(-16)=-12 | | -18+30=-4(x+5) | | x+(-24)=-38 | | -4(x+3)=4 | | 1x/19=20 | | .42*n=.6 | | 8-5x-6-9x=4 | | x(2x+5)=0 | | 6x+3=6x+2x-21 |